Intrinsic Network Pharmacology for Mapping Divergent System Trajectories: Computational Study of Rasayana Induced Restoration and Deficiency Driven Collapse - Hemanth Kumar Manikyam; Sunil K. Joshi (Archives of Current Research International, 2025)
Contemporary chronic diseases, including pervasive Vitamin D3 and B12 deficiencies, are increasingly considered failures of intricate metabolic and regulatory networks—rather than isolated biochemical imbalance. Deficiencies interrupt integrated processes such as redox signaling, immune modulation, feedback inhibition, and epigenetic stability. To investigate these system-level dysfunctions and potential cures, we use a formal 7-layer Intrinsic Network Pharmacology (INP) protocol. In contrast to regular network pharmacology, INP incorporates feedback loops, control over oxidative stress, autophagy kinetics, and homeostatic collapse and recovery dynamic simulation. In the present work, we apply the INP model to investigate two opposing situations. First, we break down the multi-level failure cascade in Vitamin D3 and B12 deficiencies, revealing breakdown points in all seven INP layers—from molecular signals up to compromised autophagy. Second, we assess the restorative potential of Chyawanprash, an Ayurvedic Rasayana with multi-herb formulation and adaptogenic activity. Through literature-derived target mapping, INP Fit Scores, and ODE simulations, we demonstrate how Chyawanprash regulates important regulators like Nrf2, SIRT1, FOXO3, Beclin1, and DNMT1. Our results demonstrate unequivocal divergence between Rasayana-supported reversal and deficiency-triggered breakdown, confirming INP as a diagnostic and therapeutic modeling platform. Although simulation-based, the outcomes imply that Rasayana preparations might exert system-level action via epigenetic network reprogramming. The present study signifies the capability of INP to guide integrative management of chronic diseases and promote nutraceutical science.